1964
DOI: 10.1084/jem.120.5.711
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactions of Pneumococcal Types

Abstract: Classification of the pneumococci has been rendered difficult by the frequent discovery of atypical strains, many of which were eventually given individual type numbers. Avery (1) recorded such variants of Type II, and of these his IIA and IIB were later designated Types V and VI (2). Chemical relationships between the three serological types were clarified in a recent series of quantitative immunochemical studies (3, 4 a-4 c, 5). Similarly, an atypical Type III strain (6) soon became Type VIII (7) (9), and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Around 1920, Avery and Heidelberger performed a series of studies establishing the bacterial capsule as a critical virulence factor of the encapsulated bacteria. [62][63][64][65][66][67][68][69] Clinical trials investigating a multivalent polysaccharide vaccine demonstrated its high efficacy in humans against pneumococcal disease. Hexavalent, 14-valent, and 23-valent pneumococcal polysaccharide vaccines (PPVs) were licensed in 1947, 1977, and 1983, respectively, for the vaccination of adults and children.…”
Section: Cps Vaccinesmentioning
confidence: 99%
“…Around 1920, Avery and Heidelberger performed a series of studies establishing the bacterial capsule as a critical virulence factor of the encapsulated bacteria. [62][63][64][65][66][67][68][69] Clinical trials investigating a multivalent polysaccharide vaccine demonstrated its high efficacy in humans against pneumococcal disease. Hexavalent, 14-valent, and 23-valent pneumococcal polysaccharide vaccines (PPVs) were licensed in 1947, 1977, and 1983, respectively, for the vaccination of adults and children.…”
Section: Cps Vaccinesmentioning
confidence: 99%
“…Quantitative estimations of antibody nitrogen were carried out as in earlier papers (Heidelberger et al, 1957;Heidelberger and Tyler, 1964). Inhibition reactions were set up in duplicate at 0°, usually with 0.10 ml of a dilution of the antiserum.…”
Section: Methodsmentioning
confidence: 99%